2005
DOI: 10.1021/ja043602h
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Particle Size on the Kinetics of CO Electrooxidation on High Surface Area Pt Catalysts

Abstract: Using high-resolution transmission electron microscopy (TEM), infrared reflection-absorption spectroscopy (IRAS), and electrochemical (EC) measurements, platinum nanoparticles ranging in size from 1 to 30 nm are characterized and their catalytic activity for CO electrooxidation is evaluated. TEM analysis reveals that Pt crystallites are not perfect cubooctahedrons, and that large particles have "rougher" surfaces than small particles, which have some fairly smooth (111) facets. The importance of "defect" sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
503
4
12

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(580 citation statements)
references
References 50 publications
61
503
4
12
Order By: Relevance
“…Although it was thought originally that surfaces with higher step densities would mimic smaller particles, the contrary was observed for particles in the nanometer range: while carbon monoxide and methanol oxidation activities increase with step density, they decrease with smaller particle size [52,53]. Furthermore, a great variance is observed in results from different groups.…”
Section: Discussionmentioning
confidence: 96%
“…Although it was thought originally that surfaces with higher step densities would mimic smaller particles, the contrary was observed for particles in the nanometer range: while carbon monoxide and methanol oxidation activities increase with step density, they decrease with smaller particle size [52,53]. Furthermore, a great variance is observed in results from different groups.…”
Section: Discussionmentioning
confidence: 96%
“…The discontinuous crystal planes or defects in the crystal structures of nanomaterials play an important role in reactive oxygen species generation; and hence nanoparticle activity is related to the available surface defect sites (Arenz et al 2005;Rajh et al 2002). A greater number of defects per unit surface area translates into greater activity.…”
Section: Discussionmentioning
confidence: 99%
“…The pztc of polycrystalline Pt was shown to be ~285 mV, changing to 245 mV for a 1nm Pt particle 35 , and they suggested it is therefore 20 conceivable that hydroxyl species could be present and stable around these potentials on active sites and defects. Further papers by Mayrhofer et al 38,39 highlighting the role of defects in the particle size effect of Pt nanoparticles also suggest that the catalytic activity for CO ads oxidation is 25 predominantly influenced by the ability of the Pt surface to dissociate water and form OH ads on defect sites, with the onset of CO ads oxidation seen at approximately 250 mV, suggesting the formation of OH ads at 250 mV. We repeated these experiments for our system and measured a 30 potential of zero total charge of 234 ±5 mV for polycrystalline platinum in 0.5 mol dm -3 sulphuric acid, which is less than the value of ~285 mV reported by Mayrhofer et al for polycrystalline Pt in 0.1 mol dm -3 perchloric acid solution 35 .…”
Section: Hydroxyl Formationmentioning
confidence: 97%
“…Assuming that there is no fourth reaction, and that the equation 1 is indeed fast, a possible explanation is that the second or third reaction cannot be considered separate from each other. Indeed, for Pt(111) it has been suggested that CO ads oxidation is accompanied by the adsorption of anions from the supporting electrolyte which affect the adsorption of OH as well as the mobility of co-adsorbed CO 62 , and for 70 platinum nanoparticles that the competitive adsorption of bisulfate anions and the existence of irregularities on the platinum surface which may serve as the active centers for OH ads formation, all play a crucial role in understanding the CO ads oxidation reaction 39 . Therefore in the absence of CO ads 75 we could expect a change in potential to give rise to noticeable currents caused by a perturbation of the equilibrium between the competitive adsorption of OH ads and bisulfate anions and it is conceivable that this could occur over extended timescales.…”
Section: Transients In the Absence Of Co Adsmentioning
confidence: 99%